Allergic manifestations of inborn errors of immunity and their impact on the diagnosis: A worldwide study - El-Sayed, Zeinab A; El-Ghoneimy, Dalia H; Ortega-Martell, José A; Radwan, Nesrine; Aldave, Juan C; Al-Herz, Waleed; Al-Nesf, Maryam A; Condino-Neto, Antonio; Cole, Theresa; Eley, Brian; Erwa, Nahla H H; Espinosa-Padilla, Sara; et al. (The World Allergy Organization journal, 2022)
BACKGROUND: Allergies have long been observed in Inborn Errors of Immunity (IEI) and might even be the first presentation resulting in delayed diagnosis or misdiagnosis in some cases. However, data on the prevalence of allergic diseases among IEI patients are limited and contradictory. OBJECTIVE: To provide a worldwide view of allergic diseases, across a broad spectrum of IEI, and their impact on the timely diagnosis of IEI. METHODS: This is a worldwide study, conceived by the World Allergy Organization (WAO) Inborn Errors of Immunity Committee. A questionnaire was developed and pilot-tested and was sent via email to collect data from 61 immunology centers known to treat pediatric and/or adult IEI patients in 41 countries. In addition, a query was submitted to The United States Immunodeficiency Network (USIDNET) at its website. RESULTS: Thirty centers in 23 countries caring for a total 8450 IEI patients responded. The USIDNET dataset included 2332 patients. Data from responders showed that a median (IQR) of 16.3% (10-28.8%) of patients experienced allergic diseases during the course of their IEI as follows: 3.6% (1.3-11.3%) had bronchial asthma, 3.6% (1.9-9.1%) atopic dermatitis, 3.0% (1.0-7.8%) allergic rhinitis, and 1.3% (0.5-3.3%) food allergy. As per the USIDNET data, the frequency of allergy among IEI patients was 68.8% (bronchial asthma in 46.9%). The percentage of IEI patients who presented initially with allergic disorders was 8% (5-25%) and diagnosis delay was reported in 7.5% (0.9-20.6%). Predominantly antibody deficiencies had the highest frequency of allergic disease followed by combined immunodeficiency with a frequency of 40.3% (19.2-62.5%) and 20.0% (10-32%) respectively. As per the data of centers, anaphylaxis occurred in 25/8450 patients (0.3%) whereas per USIDNET dataset, it occurred in 249/2332 (10.6%); drugs and food allergy were the main causes in both datasets. CONCLUSIONS: This multinational study brings to focus the relation between allergic diseases and IEI. Major allergies do occur in IEI patients but were less frequent than the general population. Initial presentation with allergy could adversely affect the timely diagnosis of IEI. There is a need for policies to raise awareness and educate primary care and other referring specialties on the association of allergic diseases with IEI. This study provides a network among centers for future prospective studies in the field.
Keywords: Anaphylaxis; Asthma; Allergic rhinitis; Omalizumab; Primary immunodeficiency; IVIG; Atopic dermatitis